(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In healthy boys from newborn to 12 years of age, the morphometric indicators of the head in the second period of childhood showed a normal growth rate compared to the period of infancy: head circumference 1.5 times (25.3%), the longitudinal size of the skull base 1.7 times (15.3% ), the transverse size of the head is 1.7 times (20.8%), the transverse size of the forehead is 1.6 times (16.2%), the vertical diameter of the head is 2.0 times (20.7%), the longitudinal size of the skull base is 1.6 times (20.2%) and the transverse size of the head increased by 1.9 times (34.6%).